Why did I buy this? An investigation of the relationship between impulse buying and post-purchase regret – a South African perspective - Grey, Natasha (The IIE, 2018)
Emerging markets in developing countries have experienced a rapid change in the retail marketplace including the expansion and development of shopping centers, increased availability of international brands, and a greater variety of products. Such changes may lead the consumers of these emerging markets to increasingly indulge in shopping. This may cause an increase in the occurrence of impulsive buying behaviours among the consumers in these developing countries. The purpose of this study is to determine whether a correlation exists between impulse buying and post-purchase regret for South African consumers. A self-developed, closed-ended questionnaire was utilized to obtain data about buyers’ impulsive purchases and whether or not these purchases resulted in regret. A sample of 25 consumers completed the questionnaires for this study. Statistical techniques were used to analyze the numerical data obtained; the researcher used a correlation analysis method as well as basic descriptive statistics. The correlation coefficient was calculated in order to determine whether impulse buying and post-purchase regret were related in some way. From the findings obtained in this study, it can be concluded that there is no relationship between impulse buying and post-purchase regret.
Keywords: impulse buying; post-purchase regret; emerging markets; South African consumers; marketplace change